Efficacy of on‐demand treatment in reducing morbidity in patients with hereditary angioedema due to C1 inhibitor deficiency. Issue 12 (30th September 2015) - Zanichelli, A.; Mansi, M.; Azin, G. M.; Wu, M. A.; Periti, G.; Casazza, G.; Vacchini, R.; Suffritti, C.; Cicardi, M.
Abstract: Background: Angioedema due to hereditary deficiency of C1 inhibitor causes temporarily disability. Guidelines recommend early on‐demand treatment of attacks to reduce morbidity. In this prospective observational study, we evaluated the efficacy of on‐demand approach. Methods: From January 2009 to August 2014, data on attacks and treatments were collected from 227 patients from our centre in Milan. Results: A total of 4244 attacks were reported; 50% were treated with approved therapies (pdC1‐INH or icatibant), 15% were with tranexamic acid, and 35% were not treated. Attack locations were peripheral cutaneous (46%), abdominal (34%), multiple (12%), facial (5%) and laryngeal (3%). Attack severities were moderate (48%), mild (28%) and severe (24%). Median attack duration (data available for 2393 attacks) with approved therapies was 10 h, significantly shorter than without treatment (45 h) or with tranexamic acid (38 h). Most of the treatments were self‐administered: 93% with icatibant and 59% with pd‐C1‐INH. Median attack duration with icatibant was 8 and 11.5 h with pd‐C1 INH. Median time from onset of symptoms to drug administration was 1 h with icatibant and 2 h with pd‐C1INH and median time from drug administration to complete resolution was 5.5 and 8 h, respectively. Second treatment was required in 12.7% of icatibant‐treated attacks and in 1.9% of pdC1‐INH‐treated attacks. Conclusion: This study provides evidence that on‐demand treatment is effective in reducing disease‐related morbidity. The use of on‐demand treatment in Italy has increased up to 50% of attacks in the last years, reflecting a better adherence to international guidelines.